The utilization of spatial statistics in a study of built-up densification in Yogyakarta urban area - Suharyadi (Faculty of Social Sciences and Humanities, UKM,Bangi, 2013)
Simple spatial statistics can be used in analyzing spatially the mean center, orientation, and standard deviation of an area with built-up densification. This research maps the built-up densification of urban areas in Yogyakarta based on the Landsat TM images of 1994, 1996, and 1998, Landsat ETM images of 2001 and 2003,and Aster images of 2006, and examines the characteristics of built-up densification in the urban areas of Yogyakarta using a spatial statistic approach.Built-up densification maps of five periods were obtained by spatial analysis of the built-up densification maps of 1994-1996, 1996-1998, 1998-2001, 2001-2003, and 2003-2006. Simple spatial statistics was applied in analyzing the built-up densification characteristics of each period. There were four spatial statistic components to describe the built-up densification, namely, the mean center position of an ellipse plane, the orientation of the ellipse, the long axis of the ellipse, and the short axis or width of the ellipse.Built-up densification maps were extracted from the spatial resolution satellite images comprising the TM Lansat satellite images, the ETM Lansat satellite images, and the Aster satellite images. Built-up densifications maps were constructed by analyzing the serial overlay operation of the built-up density maps in two consecutive years. The spatial statistic analysis of the five built-up densification maps shows dynamic variations of mean center position, orientation, and standard deviation of the built-up densification in the urban areas of Yogyakarta.